Risk and protective factors related to immediate postpartum depression in a baby-friendly hospital of Taiwan - Yun-Huei Lin; Chie-Pein Chen; Fang-Ju Sun; Chen-Yu Chen (Elsevier, 2022)
Objective: Postpartum depression (PPD) can occur in women soon after childbirth. The aim of this study was to investigate the risk and protective factors for immediate PPD in a baby-friendly hospital. Materials and methods: This cross-sectional study of singleton term pregnancies was performed at MacKay Memorial Hospital in Taiwan from January to September 2019. The enrolled women completed the Edinburgh Postnatal Depression Scale (EPDS) within 48 h after childbirth. Maternal characteristics, pregnancy and delivery factors, maternal comorbidities, supportive and childbirth factors, and neonatal outcomes were investigated. Results: Of the 1197 enrolled women, 1104 (92.23%) were at low risk (EPDS score ≤9), 66 (5.51%) were at moderate risk (EPDS score 10 to 12), and 27 (2.26%) were at high risk (EPDS score ≥13) of PPD. Significant independent risk factors for immediate PPD included the number of miscarriages (adjusted odds ratio (aOR) 1.33, 95% confidence interval (CI) 1.03-1.72, p = 0.031) and intermediate care nursery (ICN) or neonatal intensive care unit (NICU) admission (aOR 2.29, 95% CI 1.13-4.64, p = 0.022). Significant independent protective factors included planned pregnancy (aOR 0.51, 95% CI 0.28-0.92, p = 0.026), husband accompanying his wife (aOR 0.41, 95% CI 0.22-0.75, p = 0.004), early mother and newborn skin-to-skin contact (aOR 0.44, 95% CI 0.24-0.84, p = 0.012), and breastfeeding (aOR 0.23, 95% CI 0.08-0.71, p = 0.010). Conclusion: The number of miscarriages and ICN or NICU admission were independent risk factors for immediate PPD. Planned pregnancy, husband accompanying his wife, early skin-to-skin contact, and breastfeeding were independent protective factors for immediate PPD. Health care providers should pay attention to the risk factors and promote the protective factors into hospital policies to prevent the consequences of PPD.